Enhancement of oil palm empty fruit bunch char by impregnation of pyrolytic carbon from tar vapor decomposition - Rozhan, Alya Naili; Cahyono, Rochim Bakti; Nomura, Takahiro; Ani, Mohd Hanafi; Mohd. Salleh, Hamzah; Akiyama, Tomohiro; Purwanto, Hadi (American Institute of Physics, 2016)
This paper describes a technology for condensable vapor from pyrolysis (often referred to as “tar”) of oil palm empty fruit bunch, EFB, to be collected—by EFB char substrate—in the form of pyrolytic carbon to produce a value-added EFB char and to make EFB able to be utilized as a supplementary solid fuel. Chemical vapor inﬁltration method was employed at atmospheric pressure for tar vapor to undergo secondary decomposition to produce pyrolytic carbon to be deposited within porous char. Porous char in a packed bed was used as the substrate, and impregnated with pyrolytic carbon using tar vapor as a reactant. Char substrate was prepared by slowly heating coarse EFB particles in the packed bed to 400°C in nitrogen atmosphere. Tar vapor was obtained from fast pyrolysis of ﬁne EFB particles at 400–700°C, and the weight ratio of ﬁne EFB particles—the tar source—to char substrate was increased from 0.5 to 4.0. The amount of carbon contents of the resultant products by this process was compared to those without carbon deposition. After carbon deposition, EFB char has substan- tially increased in carbon contents which promise higher heating values than those of EFB char with no carbon deposition. The resultant products can be used as a partial substitute to the now depleting fossil fuels.